The Marquises of Viana: building distinction through the past (1875-1927). Issue 2 (4th May 2019) - Hernández Barral, José Miguel
ABSTRACT: In turn-of-the-century Spain, Teobaldo and José de Saavedra embodied an understanding of an aristocracy with one foot in the past and the other in the present. As holders of a recently created marquisate, their lifestyle exemplified the challenge faced by aristocrats who adopted practices and customs that were alien to them, whilst seeking to preserve elements of distinction they considered inalienable, such as dynastic history and dense family networks. The aim of this paper is to study the process of building aristocratic notability from a non-patrician origin. To this end, the profiles of the first and second Marquises of Viana are explored, paying special attention to their financial situation, social relations – particularly at Court – and a lifestyle steeped in their modern context. A key theme is their attention to art as a symbol of distinction, conceived as an instrument to leverage them to the position of the social elite of which they were becoming members. At the same time, the Marquises of Viana's careers also reveal clear connections with Europe's elite as they sought an exclusivity that would set them apart as a social group in a turbulent world.